Interdisciplinary Approaches in Modern Visual Arts Education: Theory and Practice - Kamolova E’zoza Iskandar qizi (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article examines the implementation of interdisciplinary approaches in contemporary visual arts education. It highlights how integrating knowledge from subjects such as history, biology, mathematics, and cultural studies enhances students’ artistic literacy, critical thinking, and creative competencies. Based on Shovdirov S. A.’s research, the paper explores methods including project-based learning, interactive pedagogy, and digital technologies, demonstrating how these strategies transform visual arts education into a dynamic, student-centered, and innovative process.